2021
DOI: 10.4102/safp.v63i1.5275
|View full text |Cite
|
Sign up to set email alerts
|

Are interpersonal communication skills adequately taught at postgraduate specialist level in South Africa? The neurology experience

Abstract: Background: Interpersonal communication skills by clinicians with patients, carers, fellow health professionals and legal professionals carry many unique challenges in practice. Whilst undergraduate training in communication helps with generic information receiving and information giving, uncomfortable and demanding speciality-specific issues in the various medical specialities are not covered during under- and postgraduate training.Methods: The aim of this study was to determine the self-perceived competence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 8 publications
3
6
0
Order By: Relevance
“…According to the findings of this study (Table 3), the highest mean is 4.3, indicating that 315 respondents want to share their feelings or information with their peers or that the respondents want to share information on their minds with others. This result aligns with the fundamental concept of interpersonal communication skills (Bosede, 2023;Moodley et al, 2021). The two researchers confirmed that interpersonal communication never happens with just a single speaker.…”
Section: Intercultural Sensitivitysupporting
confidence: 87%
See 1 more Smart Citation
“…According to the findings of this study (Table 3), the highest mean is 4.3, indicating that 315 respondents want to share their feelings or information with their peers or that the respondents want to share information on their minds with others. This result aligns with the fundamental concept of interpersonal communication skills (Bosede, 2023;Moodley et al, 2021). The two researchers confirmed that interpersonal communication never happens with just a single speaker.…”
Section: Intercultural Sensitivitysupporting
confidence: 87%
“…The speaker can employ affective elements to better understand the speech partner and facilitate effective communication(Bosede, 2023;Ma & Lin, 2022). Another perspective on the fundamental idea of interpersonal communication skills is provided byMoodley et al (2021), who claim that interpersonal communication skills are a person's verbal and nonverbal abilities to communicate effectively in a group setting. Furthermore,Moodley et al (2021) emphasise that effective interpersonal communication requires speakers to be sensitive to the feelings and thoughts of their speech partners.…”
mentioning
confidence: 99%
“…The lack of confidence in the ability to disclose errors, was also found in the aforementioned study of Moodley et al [20]. Among the neurology registrars participating, 28.6% deemed themselves competent in error disclosure, 38.1% reported that they lacked competence, with the remainder unsure.…”
Section: Discussionsupporting
confidence: 57%
“…Although the global medical education literature contained student appraisal of error disclosure training interventions [ 24 ], no South African study could be found that specifically asked undergraduate students to assess undergraduate training in error disclosure. However, Moodley et al [ 20 ] surveyed South African neurologists and neurology registrars. They reported an insufficient emphasis on the acquisition of complex interpersonal skills during undergraduate and postgraduate training.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation